Potensi sisa plastik elektronik sebagai sumber kepada penghasilan tenaga dan bahan mentah - Norazli Othman; Nor Ezlin Ahmad Basri; Muhd Yunus; Lariyah Mohd sidek; Nor Azizi Othman (Universiti Kebangsaan Malaysia, 2009)
Nowadays, the production of electronic equipment is one of the fastest growing industrial activities in this world. The increase use of plastic in this sector resulted in an increase of electronic plastic waste. Basically, electronic plastic material contains various chemical elements which act as a flame retardant when electronic equipment is operated. In general, the concept of recycling electronic plastic waste should be considered in order to protect the environment. For this purpose, research has been conducted to different resins of electronic plastic waste to identify the potential of electronic plastic waste as a source of raw material and energy recovery. This study was divided into two part i.e. determination of physical and chemical characteristics of plastic resins and calculation of heating value for plastic resins based on Dulong formula. Results of this research show that the average calorific value of electronic waste is 30,872.42 kJ/kg (7,375 kcal/kg). The emmission factor analysis showed that the concentration of emission value that might occur during waste management activities is below the standard set by the Environment Quality Act 1974. Basically, this research shows that electronic plastic waste has the potential to become the source of raw material and energy recovery.